Post-implementation knowledge retention of stroke: the lasting influence of FAST Heroes - Orologa, Emilia; Baskini, Maria; Tsakpounidou, Kalliopi; Keramydas, Christos; Proios, Hariklia (Frontiers in Public Health, 2024)
Background: FAST Heroes is a kindergarten-based educational program that teaches young children and their extended families (parents, grandparents) the main stroke symptoms (Face, Arm, Speech) and the timely and appropriate steps in the event of a suspected stroke (Time). However, post-campaign knowledge retention remains a challenge.The purpose of the current study was to investigate whether and to what extent grandparents' stroke knowledge is maintained 44 months after the initial implementation of the program.Methods: Forty-five participants engaged in the present study (35 women, 10 men; 72.8 §5.3) and completed an adapted version of the FAST Heroes Stroke Preparedness Questionnaire via phone calls.Results: Compared to immediately post-program implementation, respondents were still able to recall arm weakness (OR = 1.63; p = .246) and slurred speech (OR = 2.02; p = .075) as main stroke symptoms. A decrease was observed in recalling facial drooping (OR = .44; p = .042). Reporting of the appropriate course of action, was found to be increased (OR = 4.17; p < .001). Respondents remembered the emergency number to call, i.e., 112 (OR = .97; p = .947).The results showed that awareness regarding the common signs of a stroke and the importance of promptly contacting emergency services following a stroke, in the population group mostly affected by stroke, is retained. Exploring knowledge preservation in a greater sample size is warranted.